Naringenin Inhibits Adipogenesis and Reduces Insulin Sensitivity and Adiponectin Expression in Adipocytes - Richard, Allison J. (Hindawi Publishing Corporation, 2013)
Adipose tissue development and function are widely studied to examine the relationship between obesity and the metabolic syndrome. It is well documented that the inability of adipose tissue to properly increase its lipid storage capacity during the obese state can lead to metabolic dysfunction. In a blind screen of 425 botanicals, we identified naringenin as an inhibitor of adipocyte differentiation. Naringenin is one of the most abundant citrus flavonoids, and recent studies have demonstrated antihyperlipidemic capabilities. These studies have largely focused on the effects of naringenin on the liver. Our biochemical studies clearly demonstrate that naringenin inhibits adipogenesis and impairs mature fat cell function. Naringenin specifically inhibited adipogenesis in a dose-dependent fashion as judged by examining lipid accumulation and induction of adipocyte marker protein expression. In mature 3T3-L1 adipocytes, naringenin reduced the ability of insulin to induce IRS-1 tyrosine phosphorylation and substantially inhibited insulin-stimulated glucose uptake in a dose-dependent manner and over a time frame of 1.5 to 24 hours. Exposure to naringenin also inhibited adiponectin protein expression in mature murine and human adipocytes. Our studies have revealed that naringenin may have a negative impact on adipocyte-related diseases by limiting differentiation of preadipocytes, by significantly inducing insulin resistance, and by decreasing adiponectin expression in mature fat cells.